Integrated weed management in raya (Brassica juncea L.) - Kumar, Rajender; Kaur, Tarundeep (Annals of Agricultural Research, 2016)
A field experiment was conducted during rabi 2010-11 at Department of Agronomy, PAU, Ludhiana to evaluate the bioefficacy of UPH 1110, clodinafop, isoproturon and trifluralin in raya (Brassica juncea L.). The experiment comprising ten treatments replicated thrice was laid out in randomized complete block design. The results revealed that the herbicide treatments viz. Trifluralin 1l/ha fb one hand weeding at 50 days after sowing, clodinafop 0.40 kg/ha and isoproturon1.0 kg/ha were significantly superior to unweeded control in terms of weed dry matter, yield contributing characters and seed yield. Application of different doses (0.75, 1.0, 1.25 1.50 and 2.50 kg/ha) of UPH 1110 proved very effective in controlling all the weeds as no weed dry matter was recorded however, it was found phytotoxic to the crop as the seed yield was reduced significantly. Therefore, the use of herbicide UPH 1110 was not found safer for weed control in raya.